Sleep apnoea. (9th February 2016) - Jun, Jonathan C.; Chopra, Swati; Schwartz, Alan R.
Sleep apnoea is a disorder characterised by repetitive pauses in breathing during sleep caused by airway occlusion (obstructive sleep apnoea) or altered control of breathing (central sleep apnoea). In this Clinical Year in Review, we summarise high-impact research from the past year pertaining to management, diagnosis and cardio-metabolic consequences of sleep apnoea. In this year in review, we summarise the latest high-impact clinical research on obstructive and central sleep apnoea http://ow.ly/Xv0Kl